Problemáticas urbano-ambientales: un análisis desde el ecofeminismo - Anzoátegui, Micaela (2015)
Urban planning was an issue of extreme interest in antiquity and, as is known, has not been until relatively recent times in which population growth has overwhelmed most of them, built and expanded during the last two centuries. 1 The example of Mexico Df or of our own cities, especially Buenos Aires, La Plata, Rosary and Cordoba, are more than obvious. The notion of the "limits of the city" (in the multiple. The first one is posed by Aristotle, in a few lines, in the epigraph of this book, and the second one is a philosophical reflection on at least two questions. introduction it is about i) the relationship form of life/city in which we live. or In other words, we cannot rethink the city if we do not examine at the same time our "western" and "modern" form of life. The is linked to (ii) the dominant/dominated hierarchical subtext, which has been made from the dictum of francis Bacon in more, to the nature "object" of the domain of the human being, understood fundamentally as "rational".